어머니의 직업활동이 선천성 근육사경에 미치는 영향 - 김기전(Ki-Jeon Kim); 송브라이언병(Brian Byung Song) (한국콘텐츠학회 논문지, 13(9), 2013)
The Purpose of this study was to investigate the relationship between congenital muscular torticollis and maternal work activity. This study was conducted with a total of 89 outpatient pregnant women whose child presented congenital muscular torticollis at the Department of Rehabilitation of "C" Hospital in Suwon within the period from 2006 to April 30, 2011. The results were as followings: (1) The mean age at the time of giving birth was 30.09years; the proportion of pregnant women with college education or higher was high; the proportion of first delivery was 82.0%; the most common way of delivery was natural childbirth, followed by Cesarean section and vacuum extraction; the proportion of breech delivery was 20.2%; and in 82.0% of the women, the first child had congenital muscular torticollis. (2) 59.6% of the women had a career; 45.3% had engaged in professional practice or had a related job; 75.5% had worked until the third trimester of their pregnancy; 54.7% had worked for seven hours or more in a seated position; and the mean number of working hours was 8.75 (3) The level of work-related stress was a low 25% or less, and in the subdivisions of work-related stress, only the level of strained relations belonged to the upper 50% or higher. (4) For the correlation between the survey respondents' job stress and job features, stress (full score: 100 points) showed a strong positive correlation with job demand, strained relations, inadequate reward, and workplace culture. Workplace also showed a strong positive correlation with inadequate reward. Mean daily working hours showed a strong positive correlation with mean weekly working hours. 본 연구의 목적은 선천성 근육사경과 산모의 직업적 활동 간의 관련성을 알아보는 것이다. 2006년부터 2011년 4월까지 수원 "C" 병원 재활의학과를 내원한 선천성 근육사경아동의 산모 89명을 대상으로 실시하였다. 결과는 첫째, 연구대상자의 일반적 특성을 보면, 출산 평균연령은 30.09세, 교육수준은 대졸이상이 많았으며, 초산이 82.0%로 나타났으며, 자연분만, 제왕절개, 흡입분만 순이었고, 분만 시 둔위여부는 20.2%로 나타났으며, 첫째 아동이 사경인 경우가 82.0%로 나타났고, 둘째, 연구대상자의 직업적 특성에서 직장생활을 한 산모가 59.6%이고 전문가 및 관련종사자가 45.3%를 차지하였고, 직장생활을 임신 3기까지 한 산모가 75.5%로 나타났고, 주로 서서 일하는 자세보다 앉아서 일하는 자세로 앉아서 일하는 시간이 7시간 이상이 54.7%로 나타났으며, 하루 평균 근무시간은 8.75시간으로 나타났고, 셋째, 연구대상자의 직무스트레스는 하위 25%이하 수준으로 나타났으며, 하위 요인별 정도에선 관계갈등영역에서만 상위 50%이상으로 나타났다. 넷째, 연구대상자의 직무스트레스와 직업적 업무 특성간의 상관관계를 보면, 스트레스(100점 환산)와 직무스트레스의 직무요구, 관계갈등, 보상 부적절, 직장문화와 양의 상관관계가 높게 나타났으며, 직장문화와 보상 부적절간에도 양의 상관관계가 높게 나타났다. 직업적 업무 중 하루 평균 근무시간과 평균 일주일 근무시간과 양의 상관관계가 높게 나타났다.